Case report: Surgical repair of a large tracheo-esophageal fistula in a patient with post-transplant esophageal lymphoproliferative disorder. (September 2022) - Schumacher, Jonathan; Gutschow, Christian Alexander; Inci, Ilhan; Koelzer, Viktor H.; Opitz, Isabelle
Abstract: Introduction and importance: The management of large malignant tracheo-esophageal fistulas (TEF) is not standardized. Herein, we report a case with a malignant TEF associated with esophageal post-transplant lymphoproliferative disorder (PTLD) for whom we successfully performed a surgical repair. This contributes to the knowledge on how to treat large acquired malignant TEFs. Case presentation: A 69-year old male presented with a one-week history of fever, productive cough and bilateral coarse crackles. In addition, he described a weight loss of 10 kg during the past three months. The patient's history included a kidney transplantation twenty years ago. Esophagogastroduodenoscopy with a biopsy of the esophagus was performed nine days before. Histopathology showed a PTLD of diffuse large B-cell lymphoma subtype. Subsequent diagnostics revealed a progressive TEF (approx. 2.0 × 1.5 cm) 3.0 cm above the carina. PET-CT scan showed an esophagus with slight tracer uptake in the middle third (approx. 11.5 cm length, SUV max 7.4). After decision against stenting, transthoracic subtotal esophagectomy with closure of the tracheal mouth of the fistula by a pedicled flap was performed. PTLD was treated with prednisone and rituximab. Tumor progression (brain metastasis) led to death 95 days after surgery. Clinical discussion: The treatment of a malignant TEF is complex and personalized while both the consequences of the esophago-tracheal connection and those of the underlying responsible diagnosis have to be considered concurrently. In this case, we considered surgery as the best treatment option due to a relatively good prognosis of the underlying diagnosis (PTLD) and a large fistula. Esophageal or dual stenting, the treatment of choice for small malignant TEF, would have been associated with a high risk of failure due to the wide trachea, extensively dilated esophagus, proximal location and large diameter of the fistula. Conclusion: Surgery can be considered for patients with a large acquired malignant TEF and positive long-term prognosis of the underlying diagnosis. Due to the complexity of TEF management, immediate pre-operative multidisciplinary discussion is advised. Highlights: Surgical repair of a large malignant tracheo-esophageal fistula Immediate pre-operative multidisciplinary discussion is needed for large malignant trachea-esophageal fistulas. Esophageal post-transplant lymphoproliferative disorder (PTLD) of diffuse large B-cell lymphoma (DLBCL) subtype Esophagectomy and closure of the trachea by a pedicled deepithelized muscle flap